Coupling Products and Services in Design Processes: A Case Study of Smart Drip - Chou, J-R; Ha, J-L; ., Yi-ShanLai (KnE Social Sciences, 2018)
Design evolution is sequential and progressively associated with industrial and technological developments as well as human lifestyle needs. In response to current design trends toward smart products, this study presents a new perspective on product-service design to facilitate the design of innovative products. The proposed approach focuses on applying TRIZ to developing a physical product associated with its possible service supports to fulfill customers’ demands. It is based on the construct that every aspect of product and service quality should be taken into account as a whole in the early design stage. A case study of intravenous infusion(smart drip) design was conducted to demonstrate the applicability of the proposed approach. Keywords: product-service design, TRIZ, smart product, intravenous infusion, case study